2022
DOI: 10.1093/mnras/stac3198
|View full text |Cite
|
Sign up to set email alerts
|

Scrutiny of a very young, metal-poor star-forming Lyα emitter at z ≈ 3.7

Abstract: The origin of the Lyman-α (Lyα) emission in galaxies is a long-standing issue: despite several processes known to originate this line (e.g. AGN, star formation, cold accretion, shock heating), it is difficult to discriminate among these phenomena based on observations. Recent studies have suggested that the comparison of the ultraviolet (UV) and optical properties of these sources could solve the riddle. For this reason, we investigate the rest-frame UV and optical properties of A2895b, a strongly lensed Lyα-e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 149 publications
1
6
0
Order By: Relevance
“…Converting the offset separation for each source from arcseconds into kiloparsecs, we derive a median value of about 0.8 kpc. These estimates are broadly consistent with the typical Lyα-UV continuum offsets found in previous work targeting LAEs both at lower redshifts (e.g., Rasekh et al 2022) and at similar ones (e.g., Hoag et al 2019;Ribeiro et al 2020;Iani et al 2021Iani et al , 2023Claeyssens et al 2022). We present the redshift distribution and observed Lyα luminosity distribution of our final sample of LAEs in Figures 2 and 3.…”
Section: Hst/jwst Counterparts For the Lyα Emitterssupporting
confidence: 89%
“…Converting the offset separation for each source from arcseconds into kiloparsecs, we derive a median value of about 0.8 kpc. These estimates are broadly consistent with the typical Lyα-UV continuum offsets found in previous work targeting LAEs both at lower redshifts (e.g., Rasekh et al 2022) and at similar ones (e.g., Hoag et al 2019;Ribeiro et al 2020;Iani et al 2021Iani et al , 2023Claeyssens et al 2022). We present the redshift distribution and observed Lyα luminosity distribution of our final sample of LAEs in Figures 2 and 3.…”
Section: Hst/jwst Counterparts For the Lyα Emitterssupporting
confidence: 89%
“…One of the larger sources of uncertainty is the relative T e associated with emission lines of different ions, as discussed in Section 3.2, which warrants further examination to reach precision better than ;0.1 dex. The precision of our measurement could also be improved with the addition of [O II] λλ3726,3729, not covered Gustafsson et al 1999;Akerman et al 2004;Fabbian et al 2009;Nissen et al 2014); damped Lyα absorbers (DLAs; pink triangles; Cooke et al 2017); local dwarf galaxies (Berg et al 2016(Berg et al , 2019Peña-Guerrero et al 2017;Senchyna et al 2017); and z = 0 H II regions (Tsamis et al 2003;Esteban et al 2004Esteban et al , 2009Esteban et al , 2014Esteban et al , 2017García-Rojas et al 2004Peimbert et al 2005;López-Sánchez et al 2007;Toribio San Cipriano et al 2016) (z ∼ 0; cyan squares); high-redshift galaxies near cosmic noon (z ; 1.5-3.5) (orange pentagons; Fosbury et al 2003;Erb et al 2010;Christensen et al 2012;Bayliss et al 2014;James et al 2014;Stark et al 2014;Steidel et al 2016;Vanzella et al 2016;Amorín et al 2017;Berg et al 2018;Mainali et al 2020;Matthee et al 2021;Rigby et al 2021;Iani et al 2023) in our observations, which would yield improved estimates of the ICF. The [O II] doublet would also provide a better measurement of electron density n e .…”
Section: Discussionmentioning
confidence: 97%
“…Figure 4. The ( ) log C O and ( ) + 12 log O H values of our target z = 6.23 galaxy (red star) compared to other objects compiled from literature: Milky Way halo and disk stars (light-green crosses;Gustafsson et al 1999;Akerman et al 2004;Fabbian et al 2009;Nissen et al 2014); damped Lyα absorbers (DLAs; pink triangles;Cooke et al 2017); local dwarf galaxies(Berg et al 2016(Berg et al , 2019Peña-Guerrero et al 2017;Senchyna et al 2017); and z = 0 H II regions(Tsamis et al 2003;Esteban et al 2004Esteban et al , 2009Esteban et al , 2014Esteban et al , 2017García-Rojas et al 2004Peimbert et al 2005;López-Sánchez et al 2007;Toribio San Cipriano et al 2016) (z ∼ 0; cyan squares); high-redshift galaxies near cosmic noon (z ; 1.5-3.5) (orange pentagons;Fosbury et al 2003;Erb et al 2010;Christensen et al 2012;Bayliss et al 2014;James et al 2014;Stark et al 2014;Steidel et al 2016;Vanzella et al 2016;Amorín et al 2017;Berg et al 2018;Mainali et al 2020;Matthee et al 2021;Rigby et al 2021;Iani et al 2023); and a galaxy at z = 8.5 from Arellano-Córdova et al (2022) (AC22: orange circle). The ( ) log C O ratio from pure core-collapse SNe enrichment is marked with violet shading.…”
mentioning
confidence: 99%
“…Jaskot & Ravindranath (2016) found that EW C III]1906,9 peaks at very early ages (<10 Myr) and decreases (Tsamis et al 2003;Esteban et al 2004;Esteban et al 2009Esteban et al , 2014García-Rojas et al 2004;García-Rojas et al 2005;Peimbert et al 2005;López-Sánchez et al 2007;Berg et al 2016Berg et al , 2019Toribio San Cipriano et al 2016Peña-Guerrero et al 2017;Senchyna et al 2017;Ravindranath et al 2020;Senchyna et al 2021). Results at z ∼ 1.5-4 are shown as light-blue crosses (Erb et al 2010, Christensen et al 2012aBayliss et al 2014;James et al 2014;Stark et al 2014;Steidel et al 2016;Amorín et al 2017;Mainali et al 2020;Matthee et al 2021;Iani et al 2023). Note that the results obtained from stacked spectra are those from Steidel et al (2016;yellow upward-pointing triangle) and Llerena et al (2022;light-blue downward-pointing triangles).…”
Section: The Carbon-to-oxygen Abundancementioning
confidence: 98%